Hamburgs Gedächtnis - die Threse des Hamburger Rates. Die Regesten der Urkunden im Staatsarchiv der Freien und Hansestadt Hamburg Bd. I: 1350-1399 - Nolden, Nico; Marquard, Jeanine; Sarnowsky, Jürgen (Hamburg University Press, 2014)
The people of the late medieval city of Hamburg laid the foundations for power, prosperity and influence on the banks of the river Elbe. The more important the city became, the greater the need was to store important documents safely. While this task was initially only taken over by a small crate, the so-called "Threse" soon grew into a cabinet with drawers and finally into a room of the town hall.Although the holdings in the Hamburg State Archives have been handed down to a large extent in their entirety, there was no comprehensive scientific analysis. Therefore, a project of the University of Hamburg from February 2010 to March 2012 took on a contemporary edition of the collection. This volume titled "Hamburg's Memory - the Threse of the Hamburg Council, covers the years 1350 to 1399. Under the direction of Prof. Dr. Jürgen Sarnowsky, scientific authors Jeanine Marquard and Nico Nolden draw up Regesta who represent all aspects of the content, not only legally relevant ones. The annotation apparatus links the pieces with each other, explains people, places and terms and gives text-critical hints. In the registers, keywords classify the pieces 1) according to persons, 2) offices and institutions and 3) places and terms. In addition, a picture attachment shows chancellery signs, notarial instruments and other symbols."